Simultaneous acquisition of T1ρ and T2 quantification in knee cartilage: Repeatability and diurnal variation. Issue 5 (29th July 2013) - Li, Xiaojuan; Wyatt, Cory; Rivoire, Julien; Han, Eric; Chen, Weitian; Schooler, Joseph; Liang, Fei; Shet, Keerthi; Souza, Richard; Majumdar, Sharmila
Abstract : Purpose: To develop a robust sequence that combines T1ρ and T2 quantifications and to examine the in vivo repeatability and diurnal variation of T1ρ and T2 quantifications in knee cartilage. Materials and Methods: Six healthy volunteers were scanned in the morning and afternoon on 2 days using a combined T1ρ and T2 quantification sequence developed in this study. Repeatability of T1ρ and T2 quantification was estimated using root‐mean‐square coefficients‐of‐variation (RMS‐CV). T1ρ and T2 values from morning scans were compared to those from afternoon scans using paired t ‐tests. Results: The overall RMS‐CV of in vivo T1ρ and T2 quantification was 5.3% and 5.2%, respectively. The RMS‐CV ofam scans was 4.2% and 5.0% while the RMS‐CV ofpm scans was 6.0% and 6.3% for T1ρ and T2, respectively. No significant difference was found between T1ρ or T2 values in the morning and in the afternoon. Conclusion: A sequence that combines T1ρ and T2 quantification with scan time less than 10 minutes and is robust to B0 and B1 inhomogeneity was developed with excellent repeatability. For a cohort with low‐level daily activity, although no significant diurnal variation of cartilage MR relaxation times was observed, the afternoon scans had inferior repeatability compared to morning scans.J. Magn. Reson. Imaging 2014;39:1287–1293 . ©2013 Wiley Periodicals, Inc .